Analisis Tingkat Efektivitas UI/UX Sistem Informasi - Darmawan, I Gede Hadi; Kumara, I Nyoman Satya; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2024)
Good applications and information systems have an attractive interface that is easily understood by users. A good system must also be widely accepted and used by all users. Analysis of the level of effectiveness of UI/UX information systems has been using various types of different methods so that it takes a relatively long time to learn each method that is most suitable and effective. Therefore, this study aims to analyze the level of effectiveness and efficiency of the interface and user experience (UI/UX) of information systems based on various types of methods that are generally used. The method used in this research is the literature study method, by exploring and analyzing previous research related to the measurement and analysis of UI/UX in the context of information systems. The results of this research show that the level of effectiveness of UI/UX of information systems can be measured quantitatively, accompanied by statistical analysis that reflects the level of effectiveness of the 5 commonly used methods in general. In addition, this research also shows the obstacles faced in improving the effectiveness of UI/UX in information systems, as well as the importance of paying attention to good UI/UX so that users are comfortable and can easily use the system. The output of this research can provide new insights related to how much the level of effectiveness of UI/UX on information systems. And can be a reference for other studies in choosing the appropriate UI/UX effectiveness measurement analysis method.